2020
DOI: 10.1007/s11524-020-00484-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Drug Overdoses in Indianapolis

Abstract: We described the change in drug overdoses during the COVID-19 pandemic in one urban emergency medical services (EMS) system. Data was collected from Marion County, Indiana (Indianapolis), including EMS calls for service (CFS) for suspected overdose, CFS in which naloxone was administered, and fatal overdose data from the County Coroner's Office. With two sample t tests and ARIMA time series forecasting, we showed changes in the daily rates of calls (all EMS CFS, overdose CFS, and CFS in which naloxone was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(125 citation statements)
references
References 12 publications
(13 reference statements)
8
115
0
Order By: Relevance
“…A recent study confirms the role of social factors in disease spread, with each 1 point-increase in Social Vulnerability Index scores at the county-level linked to 87 excess cases and 3 additional COVID-related deaths per 100,000 people across the US (Karmakar et al, 2021). Accompanied by skyrocketing rates of mental health conditions and substance misuse (Czeisler et al, 2020;Simon et al, 2020), disproportionate increases in deaths by suicide among Black Americans (Bray et al, 2021) and increased rates of drug overdose (Friedman et al, 2020;Glober et al, 2020), the pandemic has overwhelmed health systems and pushed the health workforce and the American public to the brink.…”
Section: Introduction To the Special Issue: Social Work Practice In Tmentioning
confidence: 77%
“…A recent study confirms the role of social factors in disease spread, with each 1 point-increase in Social Vulnerability Index scores at the county-level linked to 87 excess cases and 3 additional COVID-related deaths per 100,000 people across the US (Karmakar et al, 2021). Accompanied by skyrocketing rates of mental health conditions and substance misuse (Czeisler et al, 2020;Simon et al, 2020), disproportionate increases in deaths by suicide among Black Americans (Bray et al, 2021) and increased rates of drug overdose (Friedman et al, 2020;Glober et al, 2020), the pandemic has overwhelmed health systems and pushed the health workforce and the American public to the brink.…”
Section: Introduction To the Special Issue: Social Work Practice In Tmentioning
confidence: 77%
“…This analysis revealed no evidence that COVID-19 case fatality rate and increase in opioid OD death rates are correlated. Although we used a longer study period of confirmed ODs than prior research (8, 9), the relationship between COVID-19 case fatality rates and opioid OD death rates may still evolve.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary results in California (through April 18) and Indiana (suspected ODs through July 24) show increases in daily OD deaths (8, 9). States’ OD and COVID-19 trajectories differ greatly (10), necessitating assessments of the relationship between the pandemic and ODs on a state-by-state level.…”
Section: Introductionmentioning
confidence: 98%
“…Drug overdoses accounted for 73 860 deaths between March 2019 and 2020 in the United States (U.S.), with 52 488 involving opioids 1 . Overdose deaths are implicated in the recent trend of declining life expectancy in the U.S., and the coronavirus disease 2019 (COVID‐19) pandemic may be worsening the opioid epidemic 2,3,4 . As a national crisis unfolds, health care systems must adapt to meet rapidly growing needs of patients seeking treatment for opioid use disorder (OUD).…”
Section: Introductionmentioning
confidence: 99%